Religious Revitalization among the Kiowas : the Ghost Dance, Peyote, and Christianity - Kracht, Benjamin R., 1955- (Lincoln : University of Nebraska Press, 2018)
"Framed by theories of syncretism and revitalization, "Religious Revitalization among the Kiowas" examines changes in Kiowa belief and ritual in the final decades of the nineteenth century"--
Introduction: Kiowa culture in the nineteenth century -- Christianity, peyotism, shamanism, and prophecy from the reservation period to statehood, 1869-1906 -- The ghost dance, 1890-1916 -- Christianity and peyotism in the Postallotment era -- Peyotism and Christianity after World War II -- Conclusion: indigenized Christianity and spirituality.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050
Keywords: Peyotism; Ghost dance; Kiowa Indians -- Rites and ceremonies -- 20th century; Kiowa Indians -- Rites and ceremonies -- 19th century; Kiowa Indians -- Religion -- 20th century; Kiowa Indians -- Religion -- 19th century; HISTORY -- United States -- State & Local -- Southwest (AZ, NM, OK, TX); HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; Ghost dance; Kiowa Indians -- Religion; Kiowa Indians -- Rites and ceremonies; Peyotism; 1800-1999; Electronic books